A systematic review of Randomized Controlled Trials about some non-pharmacological interventions for treatment of hypertension: Physical exercise, sodium restriction, weight and alcohol use reduction - Amobi Akonobi; Jawad Khan (Journal of Health and Social Sciences)
Introduction: Aim of this study was to systematically review available evidence to analyse how effective are some non-pharmacological interventions such as physical exercise, sodium restriction, weight reduction and alcohol reduction in the management of hypertension and to study which of them produce the greatest reduction in blood pressure. Method: A systematic literature search was carried out on Pubmed, Medline, EBSCO and EMBASE, by using several key terms and following the PRISMA statement. Original papers and randomized clinical trials, published in English between 1988 and 2010 and regarding hypertensive individuals as participants were included. The narrative synthesis system of analysis was used and the Revman 5.0 software was used to carry out heterogeneity analysis. Results: A total of 51 RCT on salt restriction (n = 11, 22%), weight loss (n = 6, 12%), alcohol reduction (n = 7, 14%), physical exercise (n = 15, 29%), or a combination of these intervention modalities (n = 12, 23%) were included in our review. 94% of them reported a significant improvement on blood pressure following these interventions, whereas 6% of them reported a statistically non-significant improvement. None of the papers reported a post-intervention deterioration. Salt restriction was found to give the greatest reduction in blood pressure. However, significant heterogeneity exists among the results of the papers reviewed in our study. Discussion and Conclusions: Our findings confirm that physical exercise, sodium restriction, weight and alcohol use reduction are four non-pharmacological interventions effective in the control of hypertension. As they involve lifestyle modification, policy interventions for primary prevention are recommended in this area.